Structural brain correlates of cognitive function in schizophrenia: A meta-analysis. (January 2022) - Khalil, Marianne; Hollander, Philippine; Raucher-Chéné, Delphine; Lepage, Martin; Lavigne, Katie M.
Highlights: Robust associations between brain structure and multiple cognitive domains observed. Functional network topography provided insight into structure-cognition associations. Highly connected regions within networks correlated with specific domains. High-level cognitive domains showed broader associations with networks. Gaps in the literature of brain-cognition associations were identified. Abstract: Schizophrenia is characterized by cognitive impairments and widespread structural brain abnormalities. Brain structure-cognition associations have been extensively studied in schizophrenia, typically involving individual cognitive domains or brain regions of interest. Findings in overlapping and diffuse brain regions may point to structural alterations in large-scale brain networks. We performed a systematic review and meta-analysis examining whether brain structure-cognition associations can be explained in terms of biologically meaningful brain networks. Of 7, 261 screened articles, 88 were included in a series of meta-analyses assessing publication bias, heterogeneity, and study quality. Significant associations were found between overall brain structure and eight MATRICS-inspired cognitive domains. Brain structure mapped onto the seven Yeo functionally defined networks and extraneous structures (amygdala, hippocampus, and cerebellum) typically showed associations with conceptually related cognitive domains, with higher-level domains (e.g., executive function, social cognition) associated with more networks. These findings synthesize the extensive literature on brain structure and cognition in schizophrenia from a contemporary network neuroscience perspective and suggest that brain structure-cognition associations in schizophrenia may follow functional network architecture.